The Value of Character Education in The Blind Side by John Lee Hancock - Melisa, Melisa; Purwanto, Andri (JEdu: Journal of English Education, 2023)
The purpose of this study is to identify and analyze the educational value of the characters featured in The Blind Side. This research analysis uses qualitative methods. The educational values contained in the film The Blind Side are religion, recognizing excellence, friendship, hard work, social care, tolerance, responsibility, and love for the motherland. The results of this study indicate that all types of educational values are contained in the film The Blind Side. From the findings of research on the value of character education in the film The Blind Side as many as 30 data, the most dominant character education value is the value of social care as much as 7 data (23.3%), religious value as much as 3 data (10%), the value of recognizing excellence 3 data (10%), friendship 3 data (10%), hard work 4 data (13%), tolerance 4 data (13%), responsibility 5 data (17%), and patriotism 1 data (3%).